Enzymatic and chemical synthesis of phosphatidylcholine regioisomers containing eicosapentaenoic acid or docosahexaenoic acid - Lyberg, Ann‐Marie; Adlercreutz, Dietlind; Adlercreutz, Patrick (European Journal of Lipid Science and Technology, 2005)
Abstract Regioselective incorporation of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) into phosphatidylcholine (PC) was carried out using enzymatic and chemical synthesis. Incorporation at the sn ‐1 position was successfully achieved by lipase‐catalysed esterification of 2‐palmitoyl‐lysophosphatidylcholine (LPC), although in most cases, the enzymes incorporated EPA and DHA at lower rates than other fatty acids. For the incorporation of DHA, Candida antarctica lipase B was the only useful enzyme, while incorporation of EPA was efficiently carried out using either this enzyme or Rhizopus arrhizus lipase. The highest yields in the lipase‐catalysed reactions were obtained at the lowest water activity (close to 0). However, by carrying out the reactions at a higher water activity of 0.22, more EPA and DHA were incorporated. Esterification of 2‐palmitoyl‐LPC with pure EPA at this water activity converted 66 mol‐% of LPC to PC using Rhizopus arrhizus lipase as catalyst. When the fatty acid was DHA and the catalyst Candida antarctica lipase B, 45 mol‐% of PC was obtained. For incorporation of EPA and DHA at the sn ‐2 position, phospholipase A 2 was used, but the reaction was very slow. Chemical coupling of 1‐palmitoyl‐LPC and EPA or DHA was more efficient, resulting in complete conversion of LPC.